Beyond the learning curve : the construction of mind - Speelman, Craig P.; Kirsner, Kim. (Oxford ; New York : Oxford University Press, 2005)
By reviewing the literature on skill acquisition, the authors propose a new theoretical approach to understanding the role of learning in behaviour. They present a new perspective on psychology - one that identifies universal principles underlying all behaviours.
6.4 Implications6.5 Recommendations; 6.6 Conclusions; References; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; R; S; T; V; W; Z.
Includes bibliographical references (pages 261-281) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Cognitive psychology; Psychologie cognitive; SCIENCE -- Cognitive Science; PSYCHOLOGY -- Cognitive Psychology; Cognitive psychology; Lerntheorie; Kognitive Psychologie; Leren; Vaardigheden; Cognitieve psychologie